Synthesis and characterization of copper coatings on polyimide membranes (PIR 003) - Velarde Loazya, Pamela Elizabeth (2022)
The formation of stable metallic/polymeric joints is a huge challenge in the materials sciences. Adhesion requires interphase that is able to specifically interact with the metallic phase. The primary amino groups exhibit copolymers as highly reactive to metal surfaces. This article will give a better understanding of the mechanisms of chemo-absorption by chemical functionalization of polyimides, as well as in the wet development of metallization of materials based on H2 reduction in polymers. And it will be evidenced by comparisons by measures of polymer/metal characterization.